Analysis of Funding, Education Performance, and Economic Growth in Indonesia - Muhammad Amir Arham; Sri Indriyani S. Dai (Jurnal Economia, 2019)
Abstract: Higher education budget allocations affect educational performance, and it also can improve human capital to boost the economic growth of a nation. Concerning this, the present study was implemented to find out the extent of educational performance effect towards the economic growth, and what variables are the most influential determinants to boost economic growth in Indonesia related to educational sector. Fixed effect approach through data panel was used to analyze the secondary data obtained from 34 provinces in Indonesia from 2014 to 2016. The result showed that educational performance in each province in Indonesia measured by using the pure participation rate of junior high school students and high school graduates and higher education graduates were able to increase the economic growth with the assumption that their skills were sufficient to increase productivity, whereas, crude participation rate of junior high school, senior high school graduates, and higher education graduates can be an obstacle to economic development. Also, the determinant factor to boost economic growth was public spending on education sector. Keywords: funding, education performance, economic growthAnalisis Pembiayaan, Kinerja Pendidikan, dan Pertumbuhan Ekonomi di IndonesiaAbstrak: Alokasi anggaran pendidikan yang makin besar memberikan efek terhadap kinerja pendidikan sekaligus memperbaiki mutu manusia yang dapat mendorong laju pertumbuhan ekonomi. Dalam kaitannya dengan hal tersebut studi ini dilakukan dengan tujuan untuk melihat seberapa besar pengaruh kinerja pendidikan terhadap pertumbuhan ekonomi dan variabel apa saja yang memiliki determinasi paling kuat mendorong pertumbuhan ekonomi di Indonesia yang terkait dengan sektor pendidikan. Metode analisis yang digunakan adalah panel data melalui pendekatan fixed effect, dengan menggunakan data sekunder untuk 34 provinsi di Indonesia selama periode 2014 – 2016. Hasil analisis menunjukkan bahwa kinerja pendidikan setiap provinsi di Indonesia yang diukur dari APM SLTP dan tamatan SLTA dapat meningkatkan pertumbuhan ekonomi dengan asumsi bahwa keterampilan mereka cukup memadai untuk meningkatkan produktivitas, sementara APK SLTP, lulusan SLTP dan lulusan perguruan tinggi dapat mengganggu pertumbuhan ekonomi. Sedangkan faktor determinan mendorong pertumbuhan ekonomi adalah variabel belanja publik sektor pendidikan. Kata Kunci: pembiayaan, kinerja pendidikan, pertumbuhan ekonomi